Trade finance and SMEs : bridging the gaps in provision (WTO GenevaCH, 2016)
Looks at the issue of accessing trade financing in detail. Brings together recent surveys and research to highlight the scale of the gaps in trade finance provision. Considers the actions that are currently being taken on this front and outlines some potential future actions.
Keywords: FINANCING